Effective service provision and partnerships in service providers for children and young people with special educational needs and disabilities: a mixed methods systematic review protocol - Tyldesley-Marshall, Natalie; Parr, Janette; Brown, Anna; Chen, Yen-Fu; Grove, Amy (Frontiers in Education, 2023)
It is widely recognised that provision of services for children and young people (CYP) with Special Educational Needs and Disabilities (SEND) are enhanced when services such as healthcare, social care, and education collaborate and interact effectively, rather than separately. In the UK, while there have been significant changes to policy and provision which support and improve collaboration, professionals responsible for implementing these changes face multiple challenges, including a lack of specific implementation guidance and a logic model or framework to illustrate how effective multi-agency working could, or should, work. This systematic review aims to identify the ‘key ingredients’ for effective multi-agency working in services for CYP with SEND; and the most effective forms of partnership working in this setting. In addition, the review will highlight interventions that lead to improved service outcomes; and the conditions in the local area (organisational or geographical) that support and encourage success. This protocol has been written following the Preferred Reporting Items for Systematic Review and Meta-Analyses Protocols guidelines. Searches will be conducted on several health, care, education and applied social science databases from the year 2012 onwards. Citation chaining will be undertaken, as will broader grey literature searching to enrich the findings. Qualitative, quantitative, and mixed methods studies will be included, assessed independently and critically appraised or assessed for risk of bias using appropriate tools based on study design. Data will be extracted using a standardised, pre-piloted data extraction form. A convergent segregated approach to synthesis and integration will be used in which the quantitative and qualitative data will be synthesised independently, and then integrated using a joint display integration matrix. Results will be of interest to educators and health and social care professionals that provide services to those with SEND. These will also be used to develop policy recommendations for how UK healthcare, social care, and education services for CYP with SEND aged 0-25 can most effectively collaborate and improve service outcomes. The review will also identify any gaps in the literature to recommend areas for future research. Funding for this review was provided by the Department for Education. PROSPERO registration: CRD42022352194